An Islamic Conception of Change - Khalil Shikaki (International Institute of Islamic Thought, 1991)
It is always refreshing to witness Muslim scholars debating one of the most important phenomena of the modern Islamic revival: the question of the "use of force." There is no doubt that this issue is deeply misunderstood and indeed misused by Islamists and non-Islamists alike. Any attempt to shed light on the subject is therefore highly appreciated and welcomed. As Muslims witness the transformation of the international political and economic system questions and expectations are raised regarding its possible impact on the Muslim world. In this context, the article which occasioned this response (AbuSulayman, 'AbdulHamid, "Guiding Light: The Qur'an and the Sunnah on Violence, Armed Struggle, and the Political Process;' AJISS 8, no. 2 [September 1991]: xi-xxxv) and the debate it is likely to generate (including the proposed World and Islamic Studies Enterprise's symposium on the subject in early 1992) is not only timely, but also highly fitting. From the outset, I would like to emphasize that I approach this topic with a great deal of academic interest and open-mindedness. Only an objective and detached analysis by, and debate among, Muslim scholars can yield a better understanding of the Islamic conception of the ' use of force." The following are some remarks that may, I hope, contribute to a better understanding of the phenomenon under discussion. On the Structure of the Debate There is a need to restructure the debate about the "use of force," sharpen its focus, clearly define its vocabulary, and place it within its proper context the Islamic conception of change. This is not a debate about "power" and "power relationships," but rather one of change and the Islamic political theory (and practice) of change. In this context, the debate is three-dimentional, for it seeks to provide answers to the following three groups of questions: a) What is the Nature and definition of change? How can we recognize change when we see it? What is the "normal" or "ideal" model which we seek to emulate and institute?; b) What instruments of change are Islamically permitted, pragmatically affordable, and most cost-effective given the nature and constraints of domestic and international politics?; and c) What means and strategies of change are most appropriate and effective and, above all, not prohibited by the Shari'ah? ...